Interpreting unwillingness to speak L2 English by Japanese EFL learners - Muroya Akiko (Open Linguistics, 2023)
This article reports on an empirical study investigating what makes Japanese learners of English as a foreign language (EFL) unwilling to speak English, regardless of their learning period, proficiency level, and location of the communication. The current study focuses on the self-perception of second language (L2) English abilities, anxiety, and interlocutors as possible causes of their unwillingness to speak L2 English, compared with first language (L1) Japanese. An online questionnaire was administered to 27 Japanese undergraduate students (age: 19–22) with non-English majors at a national university in Tokyo, Japan. The results show that the elements depressing the self-perception and willingness to speak are fundamental to managing human relationships in speaking situations, which have more impact on L2 English than L1 Japanese contexts. This is attributable to other-directedness, which has been discussed as being characteristic of Japanese and Chinese EFL learners. Furthermore, it appears plausible to assume that the other-directedness derives more from “considerations for others” than “face-saving.” Future work will further investigate what constitutes Japanese other-directedness, compared with Chinese EFL learners’.